A New and Simple Kinetic Model for Assessing the Dynamic Behavior and Simulating the Biochemical Methane Potential (Bmp) of Sewage Sludge in the Presence of Fly Ash - Huilinir-Curio, C; Montalvo-Martinez, S (John Wiley and Sons Ltd, 2019)
BACKGROUND: The modeling of anaerobic digestion of sewage sludge including the effect of fly ash has been studied only scarcely and has focused mainly on the accumulated methane (CH 4 ). The present work was aimed at assessing the complete dynamic behavior of the biochemical methane potential (BMP) of sewage sludge in the presence of fly ash, including both the liquid and gas phases. The model was calibrated and validated for BMPs using eight fly ash concentrations (10, 40, 25, 50 150, 250, 350 and 500 mg L −1 ). RESULTS: The calibration showed that the model fits well with the experimental data, with the values of the parameters falling in the range reported in the literature. The calibrated model was able to describe properly the behavior of soluble chemical oxygen demand (COD) and volatile solids in the liquid phase, with normalized root mean square error (NRMSE) and correlation coefficients (CC) ranging from 0.4052 to 0.2729 and 0.6246 to 0.8172, respectively. For the gas phase, the model was able to represent accurately the daily CH 4 production and accumulated CH 4 , with NRMSE and CC ranging from 0.8915 to 0.07194 and 0.5051 to 0.9736, respectively. CONCLUSIONS: The proposed model is robust and valid for all the tested conditions. © 2018 Society of Chemical Industry. © 2018 Society of Chemical Industry